Effect of size of latex particles on the mechanical properties of hydrogels reinforced by latex particles. Issue 26 (13th May 2019) - Liu, Li; Lv, Guangchao; Ren, Xiuyan; Li, Xinhe; Wang, Te; Dong, Jingwen; Wang, Zeyu; Wu, Guangfeng
Abstract : Herein, cationic latex particles (CL) of different particle sizes were introduced as a cross-linking center to enhance the mechanical properties of the hydrophobically-associated hydrogels (P(AAm- co -HMA)-CL). Abstract : Herein, cationic latex particles (CL) of different particle sizes were introduced as a cross-linking center to enhance the mechanical properties of the hydrophobically-associated hydrogels (P(AAm- co -HMA)-CL). Firstly, cationic polymethylmethacrylate (PMMA) latex particles were synthesized via soap-free emulsion polymerization. Subsequently, P(AAm- co -HMA)-CL hydrogels with outstanding mechanical properties were prepared using acrylamide as the monomer, hexadecyl methacrylate as the hydrophobic molecule, and CL as the cross-linking center. The size of CL had a significant effect on the mechanical properties and self-recovery properties of the P(AAm- co -HMA)-CL hydrogels. The hydrogel with larger CL size exhibited low mechanical properties due to weak hydrophobic interactions. In contrast, the hydrogel with small CL size displayed excellent mechanical properties due to an effective entanglement of the hydrophobic chains with the smaller size CL, which significantly affects the mechanical properties of the hydrogel. As a result, the maximum fracture stress and fracture strain of the hydrogel were up to 1.47 MPa and 2847%, respectively. This study can have a profound impact on the development of the technology of toughening hydrogels with latex particles.